2023
DOI: 10.14324/111.444.amps.2023v25i1.002
|View full text |Cite
|
Sign up to set email alerts
|

Greened out: mitigating the impacts of eco-gentrification through community dialogue

Abstract: Cities are increasingly employing green infrastructure, defined as a network of multi-functional open spaces within cities and between cities – including green corridors, green streets, formal parks and street trees – to promote resilience and provide clean air, flood protection and erosion control. Yet there is a growing link between these efforts and rising property values and – in some cities, including Washington, DC – displacement. This history of greening and subsequent displacement can hinder successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…As a result, they may fail to create ownership of the development process, leading to a lack of buy-in, motivation, and sustainability [28]. Micro-level community development frameworks may overlook the power dynamics and structural inequalities that underpin community issues, which can perpetuate marginalization and exclusion [29,30]. Many communities also lack the resources, capacity, and expertise needed to effectively implement and sustain community development initiatives [31].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, they may fail to create ownership of the development process, leading to a lack of buy-in, motivation, and sustainability [28]. Micro-level community development frameworks may overlook the power dynamics and structural inequalities that underpin community issues, which can perpetuate marginalization and exclusion [29,30]. Many communities also lack the resources, capacity, and expertise needed to effectively implement and sustain community development initiatives [31].…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, urban planning within a neighborhood includes a mandatory outreach meeting intended to provide residents with opportunities to engage with planners and government officials regarding a planned development (Villanueva et al, 2017). Yet often, meetings are sparsely attended due to their times, locations, and the community's belief that elected officials and developers have already brokered backroom deals (Gearin et al, 2023). Some studies have corroborated these perceptions and have found that traditional revitalization practices are often driven by city elites and elected officials who follow a predetermined project agenda shaped by private developers (Villanueva et al, 2017).…”
Section: Participation In Development and Planningmentioning
confidence: 99%